Potensi Karbon dan Jasa Lingkungan: Studi Hutan Lindung Gunung Bondang Kabupaten Murung Raya, Kalimantan Tengah, Indonesia - Eldy Indra Purnawan; Renhart Jemi; Antonius Triadi; Petrisly Perkasa (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2020)
This research was examine the potential for CO2 absorption and the provision of other ecosystem services of the Dipterocarpaceae-dominated Gunung Bondang Protection Forest in Murung Raya Regency, Central Kalimantan. The study focuses on potential carbon and ecosystem services in the form of CO2 sequestration, O2 production and payments in the form of Carbon creditsin the Gunung Bondang Protected Forest area.The study was conducted non-destructively using the parameters of the diameter and total height of the tree. The results showed the composition of the tree species was dominated by Dipterocarpaceae family, the potential biomass was 624.86 tons/ha, the potential C was 293.68 tons/ha and the potential of environmental services in the form of CO2 absorbed was 1,077.83 tons/ha, the production O2 was 786.81 tons/ha and the carbon credits was US$ 41,788/ha. Moreover, these result show the strong relevance of the Gunung Bondang Protection Forest for climate change mitigation. The protection and restoration of degraded forest parts contribute to the climate mitigation goals set by the Indonesian government, and the issuance of Carbon credits will be an important financial incentive for sustainable forest management and conservation.